2010
DOI: 10.1590/s1415-790x2010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Consumo alimentar e padrão de refeições de adolescentes, São Paulo, Brasil

Abstract: The diet of adolescents had insufficient energy intake and deficient intake of fruits and vegetables. Meal patterns were satisfactory, but breakfast should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0
55

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 19 publications
8
38
0
55
Order By: Relevance
“…Thus, this pattern has a negative effect on the healthy growth of children and adolescents, especially because it includes foods with fat, saturated fat and simple carbohydrates. While it is difficult to make direct comparisons among dietary pattern studies, findings from our study were similar to those found in other studies on Brazilian population food consumption patterns 44,45 ; these studies have shown increased consumption of manufactured products, insufficient consumption of fruits and vegetables, and increased amounts of overall fat and saturated fat in the diet.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, this pattern has a negative effect on the healthy growth of children and adolescents, especially because it includes foods with fat, saturated fat and simple carbohydrates. While it is difficult to make direct comparisons among dietary pattern studies, findings from our study were similar to those found in other studies on Brazilian population food consumption patterns 44,45 ; these studies have shown increased consumption of manufactured products, insufficient consumption of fruits and vegetables, and increased amounts of overall fat and saturated fat in the diet.…”
Section: Discussionsupporting
confidence: 89%
“…Em estudo realizado por Leal et al 33 , que objetivou avaliar o padrão de consumo alimentar de adolescentes verificou-se uma inadequação de ingestão de cálcio de 90,0% para o sexo masculino e 96,0% para o sexo feminino, dado maior do que o observado no presente estudo. Na adolescência, o consumo de cálcio adequado é fundamental, tendo em vista que o acúmulo de massa óssea ocorre desde o início da puberdade até a segunda década de vida.…”
Section: Discussionunclassified
“…Este é um grupo nutricionalmente vulnerável, considerandose suas necessidades nutricionais aumentadas, seu padrão alimentar e estilo de vida e sua suscetibilidade às influências ambientais (LEAL et al, 2010).…”
Section: Adolescênciaunclassified
“…Como consequência, ou o adolescente acaba "cedendo" ao padrão estético corporal atual, que privilegia o corpo esguio e esbelto -para as adolescentes do sexo feminino -e forte e musculoso para os adolescentes do sexo masculino, e adota comportamentos que podem desencadear o desenvolvimento de transtornos alimentares, ou adere ao consumo excessivo de refrigerantes, alimentos com conteúdo elevado de açúcares e gorduras como lanches do tipo "fast food", e a baixa ingestão de frutas, verduras e de alimentos do grupo do leite, o que pode causar excesso de peso e deficiências nutricionais (LEAL et al, 2010;SERRA e SANTOS, 2003).…”
Section: Adolescênciaunclassified
See 1 more Smart Citation